1990
DOI: 10.1679/aohc.53.81
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vitronectin in the embryonic chick heart during endocardial cell migration.

Abstract: Summary. In the early phase of heart development, the endocardial cells migrate into the truncal swellings and atrioventricular (AV) cushions, and become mesenchymal cells. Vitronectin is a glycoprotein which is thought to mediate cell migration. The present study demonstrates by immunohistochemistry the distribution of vitronectin in order to elucidate its contribution to endocardial cell migration in the developing chick heart.At HAMBURGER and MAMILTON's stage 23, the network of fibrillar material filled the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…VN is widely distributed in the ECM of many tissues in adult humans (1,2) and during embryogenesis in the mouse (30). Despite extensive prior studies suggesting a major role for VN in the developing embryo, particularly during central nervous system and heart organogenesis (7,8,30), we failed to detect any disturbance of normal growth or development in mice engineered to be completely deficient in VN. These data suggest some degree of overlap or compensation by other ECM proteins in support of these critical developmental functions.…”
Section: Targeted Disruption Of the Vn Gene In Es Cells Es Cellscontrasting
confidence: 57%
“…VN is widely distributed in the ECM of many tissues in adult humans (1,2) and during embryogenesis in the mouse (30). Despite extensive prior studies suggesting a major role for VN in the developing embryo, particularly during central nervous system and heart organogenesis (7,8,30), we failed to detect any disturbance of normal growth or development in mice engineered to be completely deficient in VN. These data suggest some degree of overlap or compensation by other ECM proteins in support of these critical developmental functions.…”
Section: Targeted Disruption Of the Vn Gene In Es Cells Es Cellscontrasting
confidence: 57%
“…Little detailed information has been published concerning vitronectin expression during cardiogenesis. Immunohistological studies using antibodies against human plasma vitronectin have revealed vitronectin expression in both the atrioventricular and conotruncal endocardial cushions in the human embryonic heart (Carnegie stages 14 to 20, Sumida et al, 1990a), chicken embryonic heart (Hamburger and Hamilton stages 23 to 29, Sumida et al, 1990b) and in the rat embryonic heart at day 13 (Sumida et al, 1992). We have expanded this work to earlier and later stages of chicken heart morphogenesis using a polyclonal antiserum prepared against the cognate chicken vitronectin antigen.…”
mentioning
confidence: 99%
“…ral tube along pharyngeal arches 3, 4, and 6 , where they provide support for the endothelium and smooth muscle lamina of the aortic arch arteries (Bockman et al, 1989;Miyagawa et al, 1989). Some cells migrate from the pharyngeal arches into the outflow tract, where they contribute to the aorticopulmonary septum, seed the cardiac ganglia, or populate the truncal cushions that differentiate into the ventricular valves and septum (Kirby et al, 1980Sumida et al, 1990). Such populations appear critical to normal septation of the cardiac outlet, since extirpation or ablation of the cardiac neural crest from the neuroectoderm results in ventricular septal defects and persistent truncus arteriosus (Nishibatake et al, 1987).…”
Section: Discussionmentioning
confidence: 99%